Sudden-Onset Widespread Body Pain (Fibromyalgia) with or without an Inciting Event: A Case Series - Hadi Shojaei; Imran Bagha; Arman Shojaei (Journal of Orthopedic and Spine Trauma, 2023)
Background: The presence of sudden-onset fibromyalgia (FM) is poorly understood, characterized, and appreciated in both previous literature and the clinical setting. In this case series, we present 10 cases of sudden-onset FM seen in a community-based pain clinic, to characterize the presentation of this condition, stemming from both external trauma and idiopathic etiology.